Reviewing the issues of managing and sharing organisation's knowledge/ Ramlee Abdul Rahman and Basri Hassan - Abdul Rahman, Ramlee; Hassan, Basri (Fakulti of Information Management, Universiti Teknologi MARA, 2011)
Knowledge sharing is essential in the implementation of any knowledge management initiatives. The real sharing required is between the employees and their co-workers. The success depends on individuals' willingness to encourage and share their organisational knowledge through internal organisational social exchanges. The process requires the element of reciprocal arrangement and trust. It requires intra-team trust and intra-team relational bonds, leadership and also intercultural training that foster regular and frequent mutual cross-cultural exchange of ideas. The advantage of knowledge management initiatives can be realised by empowering the members of the organisation. The main aim of this article is to generally discuss and assess the issue of managing and sharing organisation's knowledge by underlining the challenges. In reality if members of the organisation believe that the knowledge contributed is a strategic resource then it will create the appropriate conditions for the situation to happen. Or else, no matter how adequate the organisational structure design may be, members of the organisation will not be motivated to transfer and share the organisation's knowledge.